DEVELOPMENT OF RURAL TOURISM IN PERAK TENGAH DISTRICT BASED ON LOCAL AUTHORITY PERSPECTIVES - Isa, Mohd Ismail; Abdul Rahman, Norainah; Abdullah, Kamariah; Ahmad, Aizazi Lutfi; Mohamad, Muhammad Rijal; Rahmat, Arina; Omar, Fatin Nabila (PLANNING MALAYSIA, 2022)
Perak Tengah District has much cultural heritage potential to promote, notably in terms of village life, arts, culture, and agriculture. In order to be beneficial to the community, additional efforts should be encouraged to draw tourists to Perak, and the new attraction should be carefully defined and interpreted, especially in rural regions. Unfortunately, there is not enough support for the tourism industry's infrastructure, and the services are still not up to par. The Local Plan 2013, which promotes tourist-related products in Perak Tengah, is the foundation of the proposal to boost tourism there. This is consistent with the policies outlined in the Perak State Plan, which emphasises Perak Tengah's tourism products and integrated growth as a Perak tourism attraction. Focus group discussions with local agencies will be used in this study's qualitative research, which will be used to examine the rural development in the Perak Tengah District. The study begins by identifying the person in charge of change for each administrative area. This study is divided into five (5) main sections: the tourist destination, the tourist product, the tourist activities, the promotion of tourism, and the infrastructure for tourists, particularly in the administrative district. Based on the findings of this study, it was found that there are various potentials that local authorities can highlight. The suggestions and perceptions expressed that rural tourism can revive and improve the tourism economy in Perak Teng